Institutional educational projects in Colombia facing school integration - Lilian Caicedo Obando (Corporación Universitaria Minuto de Dios, 2004)
Nowadays, more than before people talks about the importance to pay attention to the particularity, and this concept has had different conceptions: starting with the incapacity, concept understood like the feature which make a subject different from the others. Other concept is vulnerability which require special attention by the same society that has produced this. Education is one of the most important aspects in the attention. And what is happening inside the educative institutions is not the result of only one way to face and understand the situation that imply the subjects integration since the particularity many senses are assumed in relation with the conception of: subject, school, integration. For this reason, in this article the instrumental, strategic and complex senses are analysed.